Al-Mawaad At-Ta'limiya li Kitaabi Al-Jurumiya bi Syaklin Aakhar: At-Tatwiru bi Syighati Nadzam Bahar Rajaz - Humaidi, Humaidi; Mutmainah, Mutmainah; Fahrullah, Moh. (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
Teaching materials used by teachers should be able to improve students' abilities and skills, and encourage the creation of student innovation and creativity in learning. For this reason, teachers are not only able to use teaching materials, but are also able to develop their own teaching materials and design relevant subject matter. The purpose of this study was to determine the development of learning materials for kitab jurumiyah based on nadzham bahar rajaz, as well as to determine the effectiveness of the development of teaching materials for kitab jurmiyah in the form of bahar rajaz in grade four at the shaykhona moh boarding school. Kholil bases. The type of research used is development research using the Dick and Gary model with five procedural steps, namely ADDIE. By using the pre-test and post-test evaluation to determine the effectiveness of the use of learning materials, The results of the small group trial produced a tailed T number of 0.000 and a large group of 0.001, which is smaller than 0.05, indicating that the learning materials developed are effective